Предмет: Алгебра,
автор: Ksusha202
Упростите выражение и найдите его значение:
a) 5x(x+3)-(5x+1)(x+2) при x=1,3
б)(6a-b)(a-2b)-(2a+b)(3a+2b) при а= -1,5 при b=2
Ответы
Автор ответа:
0
а)5х²+15х-5х²-10х-х-2=4х-2=4*1.3-2=5.2-2=3.2
б)6а²-12аb-ab+2b²-6a²-4ab-3ab-2b²=-20ab=-20*(-1.5)*2=30*2=60
б)6а²-12аb-ab+2b²-6a²-4ab-3ab-2b²=-20ab=-20*(-1.5)*2=30*2=60
Похожие вопросы
Предмет: Математика,
автор: avaagnia
Предмет: Литература,
автор: CAKAKAKAEGOR
Предмет: Математика,
автор: nastacvetocek122
Предмет: Геометрия,
автор: Вероника7979
Предмет: Биология,
автор: Макар777